Below-ground Dynamics in Agroforestry Systems - Akinnifesi, F K; Smucker, A J.M; Kang, B T (Annals of Arid Zone, 2016)
A lot of progress has been made in root research during the last decade in tropical agroforestry that contributes to better understanding of the interactions of roots and below-ground resource use in sequential and simultaneous systems. New tools have been developed that allow in situ measurements of root growth and interactions in woody and herbaceous species associations. There was much increase in information on root architecture. root behavior and functions of potential tree and shrub species grown in associations with crops. Root behavior is intluenced by genetic. site and management factors. The information can be utilized for minimizing competition for nutrients and moisture in agroforestry systems. especially under stress conditions, as often observed in dry zones or on acidic soils. Research is needed for more efficient utilization of below-ground growth resources by crops and/or woody species to optimize returns in various agroforestry systems. Research is also needed on the morphophysiological relationships of various root classes. on the contribution from root turn-over to soil organic matter and nutrient status. and on the need for indices for measuring root competition in agroforestry systems. Despite progress on knowledge of soil biota and faunal activities in agroforestry systems. research is needed to quantify the effects on the sustainabillty of agroforestry systems.